Water influence on the germination of forest species seeds Mimosa Caesalpiniifolia Benth (Research, Society and Development, 2021)
In semi-arid regions of Brazil, rainfall is irregular, drought is long, shallow and rocky soils, and has important forestry potential for the environment and socioeconomic status. Due to the continuous exploitation of natural resources causing significant impacts and damage to flora and fauna, for example, the extinction of unique species in the area. In order to reverse the degradation in this region, it is important that, in the production of seedlings, the necessary amount of water is made available from sowing, providing ideal humidity for a higher percentage of germination. In this context, the present research was carried out aiming to evaluate the water influence on the germination of seeds of the Caatinga forest species submitted to different irrigation levels. The experiment was carried out in the forest nursery of the Center for Rural Health and Technology/CSTR, City of the Patos – PB. For the experiment, using seeds from a forest species from the Caatinga biome: Sabiá, Mimosa caesalpiniifolia Benth. In a completely randomized design (DIC), with 5 treatments, that is, 5 different irrigation levels (L) according to the water needs of the plants (NH), being the following: L1 (100%NH); L2 (80%NH); L3(60%NH); L4(40%NH) and L5(20%NH). The following were evaluated: germination percentage (PG); germination speed index (IVG); mean time (TM) and mean speed (VM) of germination. When comparing the irrigation depth of 60% NH with that of 100% NH, there was a reduction of approximately 60% in the germination percentage, with the influence of moisture in this phase being notorious. By using 60% of the crop water requirement (NH), it obtained higher germination percentage and germination speed index, being recommended this amount of water in the germination period of this forest species.